Pembangunan Sistem Untuk Pendeteksian Code Smells Refused Bequest - Muhammad Faishal Firdaus; Bayu Priyambadha; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Code smells are a characteristic of a software that indicates problems in the code structure and system design that result in the software is being difficult to develop and maintain. The quite famous kind of code smells is refused bequest, which is a condition in the concept of inheritance that subclasses do not use the derived functionality of the superclass so as to happen inheritance rejection. Generally, code smells only can be identified through the program code structure. However, in this study developed the detection code smells in the stage of software development is design. Design is a very important phase in the software development phase because the success of a software depends on good analysis and design. At the design stage performed detection code smells with the kind of refused bequest is on the design of components, namely class diagrams design. The design of the class diagram in the .vpp format of the UML Creator Visual Paradigm application is converted into the xml language. Once converted, the xml file is detected on the detection software by parsing and finding the code smells refused bequest level referring to the smells thermometer as the measured refused bequest intensity meter. Development of this system follows the stages of software development starting from the needs analysis phase, design and implementation, as well as system testing. The tests performed on this system use testing whitebox testing for unit testing and integrase and blackbox testing for validation testing.